Preparation method of composite catalyst supported by porous functional ceramic

By modifying the Bi2MoO6/g-C3N4 composite catalyst on the porous functional ceramic, the problem of failure to effectively degrade organic foam in the prior art is solved, and a more efficient degradation effect is achieved. By optimizing the load amount of Bi2MoO6, the optimal modification amount is found to achieve efficient degradation.

CN119733543APending Publication Date: 2025-04-01SHIJIAZHUANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411880030.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art has failed to effectively combine the advantages of Bi2MoO6 and graphite phase carbon nitride (g-C3N4), and the technical solutions for degrading organic foams are insufficient.

Method used

Using a composite catalyst preparation method supported by porous functional ceramics, Bi2MoO6/g-C3N4 composite catalyst is prepared by hydrothermal method and modified onto the porous functional ceramics to optimize the load of Bi2MoO6 to improve the degradation efficiency.

Benefits of technology

A higher degradation efficiency and better catalytic effect than a single catalyst were achieved. By adjusting the loading of Bi2MoO6, the optimal modification amount was found to achieve a degradation rate of 92.22%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733543A_ABST
    Figure CN119733543A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a porous functional ceramic supported composite catalyst. The preparation method comprises the following steps: preparing Bi2MoO6; preparation of g-C3N4; the preparation method comprises the following steps: preparing Bi2MoO6 / g-C3N4 from the prepared Bi2MoO6 and the prepared g-C3N4; and the prepared Bi2MoO6 / g-C3N4 can be used for preparing the Bi2MoO6 / g-C3N4 porous functional ceramic. The composite catalyst prepared by the invention has higher degradation efficiency, and has a better catalytic effect than a single catalyst. The Bi2MoO6 / g-C3N4 composite photocatalyst is modified on porous functional ceramics, Bi2MoO6 / g-C3N4-porous functional ceramics with different modification amounts of Bi2MoO6 / g-C3N4 are prepared, and the optimal modification amount of Bi2MoO6 / g-C3N4 in the porous functional ceramics is explored by degrading MB.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite catalysts, in particular to a method for preparing a composite catalyst supported by porous functional ceramics. Background Art

[0002] The continuous increase in population and the continuous development of industrialization have caused huge pollution to the world's environment today, mainly various hazardous wastes and organic pollutants. Environmental pollution and energy crisis are urgent problems that need to be solved. With the improvement of process technology, certain achievements have been made and the overall core competitiveness has been improved. However, many problems have also been encountered, such as: serious pollution, complex structure of industrial organic dyes, high toxicity and difficult to decolorize. New photocatalytic materials are currently a hot topic internationally. Photocatalytic technology is a new, scientific, environmentally friendly and efficient technology. Semiconductor photocatalytic technology has great advantages in wastewater treatment and environmental remediation. Photosensitive materials absorb sunlight and generate a large number of active groups to degrade pollutants in water.

[0003] The study found that Bi2MoO6 is a typical Aurivillius-type layered material. Its unique layered structure increases the rate of photogenerated charge transmission and reduces the recombination of photogenerated electrons and holes. The Bi2MoO6 surface has good permeability and unique internal pores, narrow bandgap, efficient cleaning and good ion conductivity, which is effective in removing pollutants. According to the literature, bismuth molybdate is a photosensitive semiconductor with good absorption properties for sunlight, and can effectively absorb blue and red light in sunlight.

[0004] Graphite carbon nitride (g-C3N4) is a common photocatalytic material and a semiconductor. It is a non-metallic material with a unique structure, including triazine ring and heptazine ring. It has a large application market in the fields of photocatalysis and hydrogen reduction. g-C3N4 has high stability in an environment of normal temperature and pressure; it has good tolerance, acid resistance, alkali resistance and high temperature resistance. The single catalyst g-C3N4 has certain limitations in degradation. Because in the process of degradation, there is a defect that holes and photogenerated electrons are easily recombinated, which affects its degradation efficiency.

[0005] The method of using organic foam plastics can produce a better porous ceramic material, which is a new type of porous material. The process of producing porous ceramics by using organic foam plastic impregnation method started in the 1960s. In 1963, Schwartzwalde et al.'s precursor was organic foam, and the structure of organic foam was mesh-like. The slurry was evenly applied on its surface, and the structure of the porous ceramics prepared was a three-dimensional mesh structure. However, the prior art has not yet combined the advantages of Bi2MoO6 and graphite phase carbon nitride (g-C3N4) for the effective degradation of such organic foams. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing a composite catalyst supported by porous functional ceramics, so as to solve the problem that the prior art has not yet had a technical solution combining the advantages of Bi2MoO6 and graphite phase carbon nitride (g-C3N4) for effectively degrading organic foams.

[0007] To solve the above technical problems, the embodiments of the present invention provide the following technical solutions: A method for preparing a composite catalyst supported by a porous functional ceramic, comprising the following steps:

[0008] (1) Preparation of Bi2MoO6

[0009] Weigh 4.0752g of Bi(NO3)3·5H2O with an analytical balance, put it in a beaker, add 20ml of deionized water, and mark the liquid as solution A; weigh 4.2695g of (NH4)6Mo7O24·4H2O, put it in a beaker, add 20ml of deionized water, and mark the liquid as solution B. Put solutions A and B into an ultrasonic instrument and sonicate for 30 minutes;

[0010] Solution A and solution B were mixed and stirred to allow them to react fully, and the pH was adjusted to 7 with 20% NH3·H2O;

[0011] Put the fully mixed liquid in the reactor and place it in an oven at 180℃ for 6h;

[0012] After the reaction is completed, the reactor is taken out of the oven and allowed to cool naturally. After standing, the supernatant is poured out, and the sample is washed three times with deionized water, allowed to stand, and then washed three times with anhydrous ethanol. After washing, the sample is dried. The sample is placed in an evaporating dish and placed in an oven at 80°C for 3 hours. After drying, Bi2MoO6 powder is obtained.

[0013] (2) Preparation of g-C3N4

[0014] Put an appropriate amount of melamine into the ark, put it into a tube furnace, heat it to 550℃ at a rate of 5°C / min, and calcine it for 2h; after the reaction, take out the sample and place it on the laboratory table to cool, wash it with deionized water and anhydrous ethanol several times, and dry it in an oven at 80℃. The final sample is a yellow powder;

[0015] (3) Preparation of Bi2MoO6 / g-C3N4

[0016] Dissolve 5.0mmol Bi(NO3)3·5H2O in 20mL deionized water, add 2g g-C3N4, and ultrasonicate for 1h to obtain mixed solution A. Measure 0.36mmol (NH4)6Mo7O24·4H2O, put it in a beaker, add 20ml deionized water to dissolve it, and obtain solution B.

[0017] Solution A and solution B were fully mixed and stirred, and the pH was adjusted to 7 with 20% NH3·H2O. The mixture was added into an autoclave and reacted at 180°C for 6 h. After being cooled to room temperature, it was dried at 80°C.

[0018] Samples were prepared according to different modified amounts of Bi2MoO6 in the composite catalyst Bi2MoO6 / g-C3N4 sample, and the composites were marked respectively.

[0019] Preferably, the loading amounts of Bi2MoO6 in the Bi2MoO6 / g-C3N4 composite catalyst are 5%, 7.5%, 10%, 12.5% ​​and 15%, respectively.

[0020] The present invention also provides a composite catalyst supported by porous functional ceramics, which is prepared according to the above preparation method.

[0021] Furthermore, the application of the composite catalyst supported by the porous functional ceramic in the preparation of Bi2MoO6 / g-C3N4 porous functional ceramics includes:

[0022] First, a slurry consisting of alumina, wollastonite and zeolite powder was used in a ratio of 7:1.5:1.5; the additives were silicon dioxide and yttrium oxide in a ratio of 2:1; the slurry: additive = 9:1, and finally 0.3g of PVB was added and magnetic stirring was performed for 3h; suitable polyurethane foam was selected and acid-base solution was prepared, and the sponge was cut for cleaning; it was washed with deionized water and ultrasonicated 3 times for 10min each time; then, 1mol / L H2SO4 and 1mol / LNaOH were used for washing, respectively, and ultrasonically assisted for 30min each; it was dried (100℃, 3h) and placed in a tubular furnace for calcination to prepare porous functional ceramics;

[0023] The prepared porous functional ceramics were separated by sieves of different mesh sizes, and the separated porous functional ceramic blocks were placed in a reactor. The prepared Bi2MoO6 / g-C3N4 composite catalyst was added into the reactor and reacted at a temperature of 180°C for 6 hours;

[0024] After the reaction is completed, take out the sample and wait for it to cool to room temperature, then wash it three times with deionized water, let it stand, and then wash it three times with anhydrous ethanol;

[0025] After washing, the samples were placed in an evaporating dish and dried in an oven at 80°C.

[0026] The beneficial effects of the above technical solution of the present invention are as follows:

[0027] The composite catalyst prepared by the present invention has higher degradation efficiency and better catalytic effect than a single catalyst. The Bi2MoO6 / g-C3N4 composite photocatalyst is modified on porous functional ceramics to prepare Bi2MoO6 / g-C3N4-porous functional ceramics with different Bi2MoO6 / g-C3N4 modification amounts, and the optimal modification amount of Bi2MoO6 / g-C3N4 in porous functional ceramics is explored by degrading MB. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 XRD diagrams of g-C3N4, Bi2MoO6, Bi2MoO6 / g-C3N4 composite catalyst and Bi2MoO6 / g-C3N4-porous functional ceramics of the present invention;

[0029] Figure 2 This is a SEM image of the Bi2MoO6 / g-C3N4-porous functional ceramic of the present invention;

[0030] Figure 3 This is the degradation diagram of the Bi2MoO6 / g-C3N4-porous functional ceramics with different modification amounts of the present invention. DETAILED DESCRIPTION

[0031] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0032] Example 1

[0033] The present invention provides a method for preparing a composite catalyst supported by a porous functional ceramic, comprising the following steps:

[0034] (1) Preparation of Bi2MoO6

[0035] Weigh 4.0752g of Bi(NO3)3·5H2O with an analytical balance, put it in a beaker, add 20ml of deionized water, and mark the liquid as solution A; weigh 4.2695g of (NH4)6Mo7O24·4H2O, put it in a beaker, add 20ml of deionized water, and mark the liquid as solution B. Put solutions A and B into an ultrasonic instrument and sonicate for 30 minutes;

[0036] Solution A and solution B were mixed and stirred to allow them to react fully, and the pH was adjusted to 7 with 20% NH3·H2O;

[0037] Put the fully mixed liquid in the reactor and place it in an oven at 180℃ for 6h;

[0038] After the reaction is completed, the reactor is taken out of the oven and allowed to cool naturally. After standing, the supernatant is poured out, and the sample is washed three times with deionized water, allowed to stand, and then washed three times with anhydrous ethanol. After washing, the sample is dried. The sample is placed in an evaporating dish and placed in an oven at 80°C for 3 hours. After drying, Bi2MoO6 powder is obtained.

[0039] (2) Preparation of g-C3N4

[0040] Put an appropriate amount of melamine into the ark, put it into a tube furnace, heat it to 550℃ at a rate of 5°C / min, and calcine it for 2h; after the reaction, take out the sample and place it on the laboratory table to cool, wash it with deionized water and anhydrous ethanol several times, and dry it in an oven at 80℃. The final sample is a yellow powder;

[0041] (3) Preparation of Bi2MoO6 / g-C3N4

[0042] Dissolve 5.0mmol Bi(NO3)3·5H2O in 20mL deionized water, add 2g g-C3N4, and ultrasonicate for 1h to obtain mixed solution A. Measure 0.36mmol (NH4)6Mo7O24·4H2O, put it in a beaker, add 20ml deionized water to dissolve it, and obtain solution B.

[0043] Solution A and solution B were fully mixed and stirred, and the pH was adjusted to 7 with 20% NH3·H2O. The mixture was added into an autoclave and reacted at 180°C for 6 h. After being cooled to room temperature, it was dried at 80°C.

[0044] Samples were prepared according to different modified amounts of Bi2MoO6 in the composite catalyst Bi2MoO6 / g-C3N4 sample, and the composites were labeled respectively. Among them, the loading amounts of Bi2MoO6 in the Bi2MoO6 / g-C3N4 composite catalyst were 5%, 7.5%, 10%, 12.5%, and 15%, respectively.

[0045] Example 2

[0046] The application of the composite catalyst supported by the porous functional ceramic in the preparation of Bi2MoO6 / g-C3N4 porous functional ceramics includes:

[0047] A slurry consisting of alumina, wollastonite and zeolite powder was used in a ratio of 7:1.5:1.5; the additives were silicon dioxide and yttrium oxide in a ratio of 2:1; wherein, the slurry: additive = 9:1, and finally 0.3 g of PVB was added, and magnetic stirring was performed for 3 hours; suitable polyurethane foam was selected and acid-base solution was prepared, and the sponge was cut for cleaning; it was washed with deionized water and ultrasonically applied 3 times for 10 minutes each time; then, 1 mol / L H2SO4 and 1 mol / LNaOH were used for cleaning, respectively, and ultrasonically assisted for 30 minutes each; it was dried (100°C, 3 hours) and placed in a tubular furnace for calcination to prepare porous functional ceramics; the calcination procedure is shown in Tables 1 and 2.

[0048] Table 1 Calcination procedure 1

[0049]

[0050] Table 2 Calcination procedure 2

[0051]

[0052] Next, the prepared porous functional ceramics were separated using sieves of different mesh sizes, the separated porous functional ceramic blocks were placed in a reactor, and the prepared Bi2MoO6 / g-C3N4 composite catalyst was added to the reactor and reacted at 180°C for 6 hours; after the reaction, the sample was taken out and cooled to room temperature, first washed three times with deionized water, allowed to stand, and then washed three times with anhydrous ethanol; after washing, it was dried, the sample was placed in an evaporating dish, and placed in an oven at 80°C to dry.

[0053] Figure 1The XRD patterns of g-C3N4, Bi2MoO6, Bi2MoO6 / g-C3N4 composite catalyst and Bi2MoO6 / g-C3N4-porous functional ceramics are shown. As shown in Figure (a), the two different diffraction peaks of g-C3N4 are at 27.52° and 13.02°, and the corresponding diffraction planes are (002) and (100), respectively. As shown in Figure (a), the diffraction peaks of Bi2MoO6 at 11.08°, 28.24°, 32.56°, 47.1°, 55.52° and 58.42° are respectively attributed to the lattice planes of (020), (131), (200), (260), (331) and (200), and the standard card (PDF#72-1524) corresponds to them. As shown in Figure (a), the characteristic peaks of Bi2MoO6 and g-C3N4 can be found in the XRD spectrum. From this, we can see that the characteristic peaks of the catalyst are present in the composite, proving that the loading is successful. As shown in Figure (b), the characteristic peaks of Bi2MoO6 / g-C3N4 and porous functional ceramics can be seen in the XRD spectrum of Bi2MoO6 / g-C3N4-porous functional ceramics, proving that the material loaded on the ceramic is very successful.

[0054] like Figure 2 As shown: SEM photos of Bi2MoO6, g-C3N4, Bi2MoO6 / g-C3N4 and energy spectrum of Bi2MoO6 / g-C3N4. It can be seen from Figure (a) that the morphology of Bi2MoO6 is approximately a spherical structure, and the particles are evenly distributed. It can be seen from Figure (b) that g-C3N4 is a block-like stacked layered structure. Figure (c) is a SEM photo of the composite catalyst, which shows that there are spherical Bi2MoO6 and block-like stacked g-C3N4. It can be seen from Figure (d) that there are C, N, O, Mo and Bi elements in the composite, among which elements C and N are elements of g-C3N4, and elements O, Mo and Bi are elements of Bi2MoO6, which more rigorously proves the elemental composition of the Bi2MoO6 / g-C3N4 composite catalyst. Figures (e) and (f) are SEM images of Bi2MoO6 / g-C3N4-porous functional ceramics, where the insets are photos of Bi2MoO6 / g-C3N4-porous functional ceramics.

[0055] like Figure 3It is the degradation rate of porous functional ceramics with different modification amounts of Bi2MoO6 / g-C3N4. It can be seen from the figure that with the increase of the loading amount, the degradation rate also increases. When the loading amount is 20%, the degradation effect of porous functional ceramics is the best, and the degradation rate is 92.22%. It may be because with the increase of the loading amount, the recombination rate of photogenerated electrons and holes in the composite catalyst decreases, and the energy band structure matches, which is conducive to carrier transport. When the loading amount exceeds 20%, the degradation rate begins to decrease when the loading amount is increased. The reason for the decrease in degradation rate may be that the loading amount has reached saturation and can no longer continue to be loaded on the surface of porous functional ceramics, which in turn affects its degradation rate.

[0056] Based on the above content, the method used in the preparation of Bi2MoO6 / g-C3N4-porous functional ceramics of the present invention adopts a hydrothermal method, and the material composition, micromorphology and particle size of Bi2MoO6, g-C3N4 and Bi2MoO6 / g-C3N4 with different modified amounts are preliminarily determined. The method for preparing composite catalysts with different proportions adopts a hydrothermal method, explores the degradation effect of composite catalysts under different proportions, and finds the optimal modification amount of composite photocatalyst by degrading MB. It can be seen from the control experiment that the composite catalyst has a higher degradation efficiency and a better catalytic effect than a single catalyst. The Bi2MoO6 / g-C3N4 composite photocatalyst is modified onto porous functional ceramics to prepare Bi2MoO6 / g-C3N4-porous functional ceramics with different Bi2MoO6 / g-C3N4 modified amounts, and the optimal modification amount of Bi2MoO6 / g-C3N4 in porous functional ceramics is explored by degrading MB.

[0057] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite catalyst supported by a porous functional ceramic, characterized in that: The following steps are involved: Preparation of Bi2MoO6 Weigh 4.0752 g of Bi(NO3)3·5H2O with an analytical balance, put it in a beaker, add 20 ml of deionized water, and mark the liquid as solution A; weigh 4.2695 g of (NH4)6Mo7O24·4H2O, put it in a beaker, add 20 ml of deionized water, and mark the liquid as solution B. Put solutions A and B into an ultrasonic instrument and sonicate for 30 min; Solution A and solution B were mixed and stirred to allow them to react fully, and the pH was adjusted to 7 with 20% NH3·H2O; Place the fully mixed liquid in a reactor and place it in an oven at 180 °C for 6 h; After the reaction is completed, the reactor is taken out of the oven and allowed to cool naturally. After standing, the supernatant is poured out, and the sample is washed three times with deionized water, allowed to stand, and then washed three times with anhydrous ethanol. After washing, the sample is dried. The sample is placed in an evaporating dish and placed in an oven at 80 °C for 3 h. After drying, Bi2MoO6 powder is obtained. Preparation of g-C3N4 Put an appropriate amount of melamine into the ark, put it into a tube furnace, heat it to 550 °C at a rate of 5 °C / min, and calcine for 2 h; after the reaction, take out the sample and place it on the laboratory bench to cool, wash it with deionized water and anhydrous ethanol several times, and dry it in an oven at 80 °C. The final sample is a yellow powder; Preparation of Bi2MoO6 / g-C3N4 Dissolve 5.0 mmol Bi(NO3)3·5H2O in 20 mL deionized water, add 2 g of g-C3N4, and ultrasonicate for 1 h to obtain mixed solution A. Measure 0.36 mmol of (NH4)6Mo7O24·4H2O, place it in a beaker, and add 20 ml of deionized water to dissolve it, to obtain solution B. Solution A and solution B were fully mixed and stirred, and the pH was adjusted to 7 with 20% NH3·H2O. The mixture was added into an autoclave and reacted at 180 °C for 6 h. After being taken out and cooled to room temperature, it was dried at 80 °C. Samples were prepared according to different modified amounts of Bi2MoO6 in the composite catalyst Bi2MoO6 / g-C3N4 sample, and the composites were marked respectively.

2. The method for preparing a composite catalyst supported by a porous functional ceramic according to claim 1, characterized in that: The loading amounts of Bi2MoO6 in the Bi2MoO6 / g-C3N4 composite catalyst are 5%, 7.5%, 10%, 12.5% ​​and 15%, respectively.

3. A composite catalyst supported by porous functional ceramics, characterized in that: Prepared according to the preparation method of claim 1 or 2.

4. The use of the composite catalyst supported by the porous functional ceramics according to claim 3 in the preparation of Bi2MoO6 / g-C3N4 porous functional ceramics, characterized in that: include: First, a slurry consisting of alumina, wollastonite and zeolite powder is used in a ratio of 7:1.5:1.5; the additives are silicon dioxide and yttrium oxide in a ratio of 2:1; wherein the slurry: Additive = 9:1, finally add 0.3 g of PVB, and stir magnetically for 3 h; select appropriate polyurethane foam and prepare acid and alkali solution, cut the sponge for cleaning; wash with deionized water, ultrasonic 3 times, each time for 10 min; then, use 1 mol / L H2SO4 and 1 mol / L NaOH for cleaning, ultrasonic assisted for 30 min respectively; dry (100 °C, 3 h) and place in a tubular furnace for calcination to prepare porous functional ceramics; The prepared porous functional ceramics were separated using sieves of different mesh sizes, and the separated porous functional ceramic blocks were placed in a reactor. The prepared Bi2MoO6 / g-C3N4 composite catalyst was added into the reactor and reacted at a temperature of 180 °C for 6 h; After the reaction is completed, take out the sample and wait for it to cool to room temperature, then wash it three times with deionized water, let it stand, and then wash it three times with anhydrous ethanol; After washing, the samples were placed in an evaporating dish and dried in an oven at 80 °C.